2010
DOI: 10.1016/j.yebeh.2010.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral evaluation of adult rats exposed in utero to maternal epileptic seizures

Abstract: We investigated the effects of exposure to maternal convulsive seizures in utero on the behavior of offspring. An epilepsy model was induced in female rats by administration of pilocarpine. Seizure frequency was evaluated for 60 days. The rats were then allowed to mate, and seizure frequency during pregnancy was recorded and compared with prepregnancy frequency. After birth, placentas of mothers were submitted for histopathological analysis. The behavior of the offspring was evaluated 3 months after birth. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 23 publications
5
16
0
Order By: Relevance
“…In agreement with these results, do Vale et al (2010) observed minimal anatomical changes in the hippocampus of offspring of epileptic dams, except the abnormal development of parvalbumin-positive interneurons. Interestingly, in our study, the frequency of seizures was higher during mid-gestation, corroborating previous findings by Lima et al (2010).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In agreement with these results, do Vale et al (2010) observed minimal anatomical changes in the hippocampus of offspring of epileptic dams, except the abnormal development of parvalbumin-positive interneurons. Interestingly, in our study, the frequency of seizures was higher during mid-gestation, corroborating previous findings by Lima et al (2010).…”
Section: Discussionsupporting
confidence: 89%
“…It has been suggested that seizures during pregnancy reduce the oxygen supply to the fetal circulation, which could affect intrauterine development. In fact, Lima et al (2010) observed areas of infarction in the placenta of females with epilepsy, suggesting the occurrence of low blood flow. Antenatal hypoxia-ischemia is one major cause of fetal brain damage, with long-term behavioral consequences (Dubovický 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations